2009
DOI: 10.1103/physrevd.79.112002
|View full text |Cite
|
Sign up to set email alerts
|

Search for new particles decaying into dijets in proton-antiproton collisions ats=1.96TeV

Abstract: We present a search for new particles which produce narrow two-jet (dijet) resonances using protonantiproton collision data corresponding to an integrated luminosity of 1:13 fb À1 collected with the CDF II detector. The measured dijet mass spectrum is found to be consistent with next-to-leading-order perturbative QCD predictions, and no significant evidence of new particles is found. We set upper limits at the 95% confidence level on cross sections times the branching fraction for the production of new particl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
150
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(151 citation statements)
references
References 46 publications
0
150
1
Order By: Relevance
“…It has been shown that this function fits well the QCD mass distribution of PYTHIA, HERWIG, and NLO pQCD predictions for pp collisions at √ s = 1.96 TeV [6]. Also, MC studies using PYTHIA in ATLAS [7] demonstrate that this function describes the QCD mass spectrum well, with a χ 2 /NDF of 27.0/22 over the dijet mass range of 200 < m j j < 1900 GeV, as is shown in Figure 3.…”
Section: Background Determinationmentioning
confidence: 53%
“…It has been shown that this function fits well the QCD mass distribution of PYTHIA, HERWIG, and NLO pQCD predictions for pp collisions at √ s = 1.96 TeV [6]. Also, MC studies using PYTHIA in ATLAS [7] demonstrate that this function describes the QCD mass spectrum well, with a χ 2 /NDF of 27.0/22 over the dijet mass range of 200 < m j j < 1900 GeV, as is shown in Figure 3.…”
Section: Background Determinationmentioning
confidence: 53%
“…CDF has published studies both of the angular distribution of the dijets [8] and of a possible resonant structure in the dijet mass spectrum [9]. In both cases it is nontrivial for us to compare these results with the signal we might expect.…”
Section: Scalar Exchangementioning
confidence: 73%
“…All this is preliminary, however, also because the resonance may be within the accessible range. Indeed the same resonance search in [9] could be of importance to us. The problem in this case, however, is that the published limits concern only narrow resonances, when the width is within the resolution, while we are dealing with the opposite case.…”
Section: Scalar Exchangementioning
confidence: 99%
“…These results are consistent with the SM predictions allowing to place an upper limit on the signal cross section times the corresponding branching fraction of the process pp → Z → µ + µ − (e + e − ). 8 There are also searches for dijet resonances and monojets plus missing energy that receive additional contributions from the presence of a Z boson, both at the LHC and Tevatron colliders, and hence, they can be used to place constraints on this kind of models as well [71][72][73].…”
Section: Jhep04(2015)175mentioning
confidence: 99%